Predictive validity of clinical AUDIT‐C alcohol screening scores and changes in scores for three objective alcohol‐related outcomes in a Veterans Affairs population. (2nd August 2016) - Bradley, Katharine A.; Rubinsky, Anna D.; Lapham, Gwen T.; Berger, Douglas; Bryson, Christopher; Achtmeyer, Carol; Hawkins, Eric J.; Chavez, Laura J.; Williams, Emily C.; Kivlahan, Daniel R.
Abstract: Aims: To evaluate the association between Alcohol Use Disorder Identification Test–Consumption (AUDIT‐C) alcohol screening scores, collected as part of routine clinical care, and three outcomes in the following year (Aim 1), and the association between changes in AUDIT‐C risk group at 1‐year follow‐up and the same outcomes in the subsequent year (Aim 2). Design: Cohort study. Setting: Twenty‐four US Veterans Affairs (VA) healthcare systems (2004–07), before systematic implementation of brief intervention. Participants: A total of 486 115 out‐patients with AUDIT‐Cs documented in their electronic health records (EHRs) on two occasions ≥ 12 months apart ('baseline' and 'follow‐up'). Measurements: Independent measures were baseline AUDIT‐C scores and change in standard AUDIT‐C risk groups (no use, low‐risk use and mild, moderate, severe misuse) from baseline to follow‐up. Outcome measures were (1) high‐density lipoprotein cholesterol (HDL), (2) alcohol‐related gastrointestinal hospitalizations ('GI hospitalizations') and (3) physical trauma, each in the years after baseline and follow‐up. Findings: Baseline AUDIT‐C scores had a positive association with outcomes in the following year. Across AUDIT‐C scores 0–12, mean HDL ranged from 41.4 [95% confidence interval (CI) = 41.3–41.5] to 53.5 (95% CI = 51.4–55.6) mg/l, and probabilities of GI hospitalizations from 0.49% (95% CI = 0.48–0.51%) to 1.8% (95% CI = 1.3–2.3%) and trauma from 3.0% (95% CI = 2.95–3.06%) to 6.0% (95% CI = 5.2–6.8%). At follow‐up, patients who increased to moderate or severe alcohol misuse had consistently higher mean HDL and probabilities of subsequent GI hospitalizations or trauma compared with those who did not ( P ‐values all < 0.05). For example, among those with baseline low‐risk use, in those with persistent low‐risk use versus severe misuse at follow‐up, the probabilities of subsequent trauma were 2.65% (95% CI = 2.54–2.75%) versus 5.15% (95% CI = 3.86–6.45%), respectively. However, for patients who decreased to lower AUDIT‐C risk groups at follow‐up, findings were inconsistent across outcomes, with only mean HDL decreasing in most groups that decreased use ( P ‐values all < 0.05). Conclusions: When AUDIT‐C screening is conducted in clinical settings, baseline AUDIT‐C scores and score increases to moderate–severe alcohol misuse at follow‐up screening appear to have predictive validity for HDL cholesterol, alcohol‐related gastrointestinal hospitalizations and physical trauma. Decreasing AUDIT‐C scores collected in clinical settings appear to have predictive validity for only HDL.